ESTSS and ISTSS: “heterozygous twins” - Gersons, Berthold P. R. (Co-Action Publishing, 2013)
The development of traumatic stress studies during the past decades has much profited from professionals from the United States and from Europe. However, these professional societies, the International Society for Traumatic Stress Studies and the European Society for Traumatic Stress Studies (ESTSS) still struggle to find an equal common pathway. This is a personal retrospective view of Berthold Gersons, past president of ESTSS on behalf of the 20th anniversary of ESTSS.